2020
DOI: 10.3390/genes11030259
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA H19 Promotes Porcine Satellite Cell Differentiation by Interacting with TDP43

Abstract: Long non-coding RNAs (lncRNAs) have been implicated in fundamental and diverse biological processes, including myogenesis. However, the molecular mechanisms involved in this process remain largely unexplored. This study found that H19 affected the differentiation of porcine satellite cells (PSCs) by directly binding to the DNA/RNA-binding protein TDP43. Functional analyses showed that TDP43 knockdown decreased PSC differentiation, whereas TDP43 overexpression exerted opposite effects in vitro. Furthermore, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…There is increasing evidence that lncRNAs are functionally conserved among species. 15 , 23 , 24 The functional conservation of lncRNAs among species can be explained as follows: lncRNAs have conserved binding domains and secondary or higher structures. For example, the 2D structure of the A region of Xist can recruit components of PRC2 that are needed for X‐chromosome inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that lncRNAs are functionally conserved among species. 15 , 23 , 24 The functional conservation of lncRNAs among species can be explained as follows: lncRNAs have conserved binding domains and secondary or higher structures. For example, the 2D structure of the A region of Xist can recruit components of PRC2 that are needed for X‐chromosome inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al found that the lncRNA MSTRG.42019 was associated with skeletal muscle fiber-type switching in pigs [ 53 ]. Several lncRNAs, such as LncMyoD , SAM , H19 , and CTTN-IT1 , affect the activity of satellite cells in mice, pigs, and sheep [ 54 , 55 , 56 , 57 ]. The in vivo silencing of Pvt1 results in increases in the size and number of mitochondria [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li reported that 2310043L19Rik (lnc-231) inhibited differentiation and promoted proliferation of myoblasts as ceRNA to target miR-125a-5p, thereby inhibiting the function of E2F3 mRNA (Li et al, 2020b ). Conversely, H19 can act as a molecular scaffold to recruit TDP43 to promoters of MyoD and activate transcription, thereby promoting porcine SC differentiation (Li et al, 2020a ). Furthermore, some lncRNAs can give rise to functional micropeptides.…”
Section: Lncrnas In Myogenesismentioning
confidence: 99%